2020
DOI: 10.3897/mycokeys.62.47425
|View full text |Cite
|
Sign up to set email alerts
|

Identification of six Cytospora species on Chinese chestnut in China

Abstract: Chinese chestnut (Castanea mollissima) is an important crop tree species in China. In the present study, Cytospora specimens were collected from Chinese chestnut trees and identified using molecular data of combined ITS, LSU, ACT and RPB2 loci, as well as morphological features. As a result, two new Cytospora species and four new host records were confirmed, viz. C. kuanchengensissp. nov., C. xinglongensissp. nov., C. ceratospermopsis, C. leucostoma, C. myrtagena and C. schulzeri.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…In China, previous studies have revealed a high fungal diversity associated with chestnut branch cankers. For example, three Coryneum species [ 8 ], two Cryphonectria species [ 2 ], six Cytospora species and seven Dendrostoma species were described from the cankered branches [ 9 , 10 ]. In addition, some cryptic species were discovered, such as Aurantiosacculus castaneae [ 2 ], Endothia chinensis [ 2 ], Melanops castaneicola and Neopseudomelanconis castaneae [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In China, previous studies have revealed a high fungal diversity associated with chestnut branch cankers. For example, three Coryneum species [ 8 ], two Cryphonectria species [ 2 ], six Cytospora species and seven Dendrostoma species were described from the cankered branches [ 9 , 10 ]. In addition, some cryptic species were discovered, such as Aurantiosacculus castaneae [ 2 ], Endothia chinensis [ 2 ], Melanops castaneicola and Neopseudomelanconis castaneae [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the species occurrence may be related to geographical and environmental factors rather than host specificity (Fan et al, 2014a , b ; Fan et al, 2015a , b ). To more accurately identify Cytospora species, several species have been described based on morphological observations and multilocus phylogeny in recent studies (Yang et al, 2015 ; Lawrence et al, 2017 , 2018 ; Zhu et al, 2018 , 2020 ; Fan et al, 2020 ; Jiang et al, 2020 ; Shang et al, 2020 ). Norphanphoun et al ( 2017 ) used four loci to describe 14 new species isolated from Rosa, Salix , and Sorbus .…”
Section: Introductionmentioning
confidence: 99%
“…A total of 144 strains from Iran represented 20 species of Cytospora based on ITS phylogeny ( Fotouhifar et al, 2010 ). Later, many species were described based on multilocus phylogeny in recent studies ( Fan et al, 2014a , b , 2015a , b ; Yang et al, 2015 ; Lawrence et al, 2017 , 2018 ; Zhu et al, 2018 , 2020 ; Jiang et al, 2020 ; Shang et al, 2020 ). Fan et al (2020) provided an assessment of 52 species of Cytospora in China using a six-locus phylogeny [internal transcribed spacer (ITS), large nuclear ribosomal RNA subunit (LSU), actin ( act ), RNA polymerase II subunit ( rpb2 ), translation elongation factor 1-α ( tef1- α), and beta-tubulin ( tub2 )].…”
Section: Introductionmentioning
confidence: 99%